Indonesian master students’ motivation and metacognitive strategies in academic writing - Gloria, Gloria; Mbato, Concilianus Laos (Universitas Islam Negeri Banda Aceh, 2023)
In higher education, students must complete their studies by writing academic papers and publishing research articles. Students might have experienced ups and downs because not all students like to write, especially academic papers. Good writers use metacognitive strategies and maintain their motivation to improve their writing skills. The current researchers conducted a mixed-method study to determine master students’ motivation and metacognitive strategies in their writing and how metacognitive strategies affected their motivation in academic writing. The participants were 40 master’s students of English Education at Sanata Dharma University, Yogyakarta. The researchers gathered the data using a close-ended questionnaire on Academic Writing Motivation and Metacognitive Strategy and a semi-structured interview. The first finding revealed that master students were more extrinsically motivated to write academic papers. However, both intrinsic and extrinsic motivation were involved in their success. The second finding indicated that master students were conscious of metacognitive strategies applying the stages namely planning, monitoring, and evaluating in different ways in writing. Data analysis also revealed a strong positive correlation between motivation and metacognitive strategies. They agreed that motivation and metacognitive strategy were connected in academic writing to achieve goals. Therefore, the results underlined that students must activate and maintain motivation and metacognitive strategy during the writing process. The implications and future research opportunities were discussed in this research.